2003
DOI: 10.1046/j.1464-410x.2003.04178.x
|View full text |Cite
|
Sign up to set email alerts
|

Posterior urethral valves: prognostic factors

Abstract: The most significant prognostic factor for the future development of CRF is the GFR at 1 year old. The onset of proteinuria during the follow-up is associated with a worse prognosis. Echogenic renal changes may help to identify those dysplastic kidneys that will develop RI. Neonatal boys in RI who underwent pyelo-ureterostomy had better RF during the first years of life than those who underwent valve ablation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
42
4
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(57 citation statements)
references
References 17 publications
7
42
4
4
Order By: Relevance
“…The associated obstructive nephropathy and renal dysplasia are the leading cause of ESRD in surviving children (2). Approximately 20%-30% of affected children progress to ESRD in the first decade of life, and the majority progress to CKD (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…The associated obstructive nephropathy and renal dysplasia are the leading cause of ESRD in surviving children (2). Approximately 20%-30% of affected children progress to ESRD in the first decade of life, and the majority progress to CKD (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…7,32 CKD. 22,23 In 2003, Osama demonstrated that when the clearance of creatinine was lower than 60 mL/min/1.73 m 2 , the prognosis for renal failure in the future would be at approximately 50%, while for creatinine clearance above 90 mL/min/1.73 m 2 , the incidence of renal failure would decrease to 27%. 17 Some other factors are also considered in assessing the risk of developing CKD in the future or its progression to ESRD.…”
Section: Voiding Cystourethrographymentioning
confidence: 99%
“…3,7,8 Floroskopi altında yapılan VCUG, PUV ve VUR şüphesi olan hastalarda en sık başvurulan ve altın standart olan bir tetkiktir; fakat suprapubik veya üretral yolla mesane kateterizasyonu gerektiren bir tetkik olduğu için invaziv ve ağrılıdır. 12,13 Mesane kateterizasyonunu takiben seyreltilmiş radyoopak sıvı 40-70 cmH 2 O basıncı ile mesaneye verilir. Hastadan mesane dolumu esnasında ve üretra kateteri çıkarıldıktan sonra işeme esnasında radyografik görüntüler alınır.…”
Section: Bulgularunclassified
“…Literatürle kıyaslandığında VUR görülme sıklığının benzer olduğu görüldü. [7][8][9][13][14][15] VUR görülmeyen 14 (%35) olguda posterior üretra dilatasyonu mevcut olup, aynı zamanda mesane kapasitesi artmıştı.…”
Section: Bulgularunclassified
See 1 more Smart Citation